HLA-A*02 alleles are associated with tetanus antitoxin-induced exanthematous drug eruptions in Chinese patients. Issue 12 (December 2016) - Yan, Sijia; Chen, Sheng-an; Zhang, Wen; Yang, Fanping; Yang, Ying; Zhu, Qinyuan; Zhu, Huizhong; Sun, Xinfen; Jiang, Menglin; Su, Yu; Zhang, Lirong; Xing, Qinghe; et al.
Abstract : Objective: Tetanus antitoxin (TAT) is an effective antitetanus medicine, but may sometimes cause adverse drug reactions such as rapid-onset anaphylactic shock and late-onset cutaneous adverse drug reactions, including exanthematous drug eruptions (EDE). Human leukocyte antigen ( HLA ) class I alleles are strongly associated with different types of cutaneous adverse drug reactions. This study aimed to assess whether there is an association between TAT-induced EDE and HLA-A, HLA-B, and HLA-C alleles in the Chinese Han population. Patients and methods: We carried out an association study in 15 patients with TAT-induced EDE and two groups of general Han Chinese patients. Allele-level genotypes of the HLA-A, HLA-B, and HLA-C genes of each patient were determined using the PCR-sequence-specific oligonucleotides method. Results: The carrier frequency of HLA serotype A2 was significantly higher in the TAT-induced EDE patients than in the general Han Chinese study participants from the human major histocompatibility complex database [ n =283, odds ratio (OR)=6.93; P =0.0061]. Particularly, the carrier frequency of three A2 alleles, including HLA-A*02:01, HLA-A*02:06, and HLA-A*02:07, is significantly higher than that of the control group (OR=14.40; P =2.4×10 −5 ). Furthermore, HLA-B*39:01 was in complete linkage disequilibrium with HLA-A*02:06 in the case patients. Consequently, the distribution of the HLA-A*02:06 / -B*39:01 haplotype was also significantly different in the cases and the controls (OR=105.00; P =0.0024). Conclusion: The HLA-A*02:06 / -B*39:01 haplotype is a potential genetic marker for the TAT-induced EDE. Furthermore, the HLA-A2 serotype, especially three alleles A*02:01, A*02:06, and A*02:07, was identified to be associated with the TAT-induced EDE in the Han Chinese population for the first time. Abstract : Supplemental Digital Content is available in the text.